2013
DOI: 10.1371/journal.pmed.1001387
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing versus Traditional Genotyping for Investigation of a Mycobacterium tuberculosis Outbreak: A Longitudinal Molecular Epidemiological Study

Abstract: In an outbreak investigation of Mycobacterium tuberculosis comparing whole genome sequencing (WGS) with traditional genotyping, Stefan Niemann and colleagues found that classical genotyping falsely clustered some strains, and WGS better reflected contact tracing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
414
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 453 publications
(451 citation statements)
references
References 34 publications
19
414
2
1
Order By: Relevance
“…137,138 As with other typing methods, transmission of M tuberculosis strains is measured by the relatedness of each strain's whole-genome sequencing results. Recent reports have suggested that strains differing by less than 10 single nucleotide variations reflect transmission 46,74,137,139,140 (figure 4). Deciphering tuberculosis transmission dynamics is crucial for the optimisation of local and global control measures and the early detection of MDR and XDR outbreaks.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…137,138 As with other typing methods, transmission of M tuberculosis strains is measured by the relatedness of each strain's whole-genome sequencing results. Recent reports have suggested that strains differing by less than 10 single nucleotide variations reflect transmission 46,74,137,139,140 (figure 4). Deciphering tuberculosis transmission dynamics is crucial for the optimisation of local and global control measures and the early detection of MDR and XDR outbreaks.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…Short-term evolutionary rate in M. tuberculosis complex has been estimated to be between 0.3 and 0.5 punctual mutations per genome per year (also referred to as Single Nucleotide Polymorphism or SNP per genome per year) which corresponds to an annual rate per site of 6.8 x 10 -8 to 1.1 x 10 -7 (Bryant et al, 2013;Ford et al, 2011;Guerra-Assuncao et al, 2015;Roetzer et al, 2013;Walker et al, 2013). Mutation rate was also assessed directly using whole genome sequence of a tuberculosis sample extracted from a 1,000-year old Peruvian mummy: it was measured as 4.8 x 10 -8 SNP/site/year i.e.…”
Section: Current Knowledge On Tuberculosis Evolution Ratementioning
confidence: 99%
“…Mycobacterium tuberculosis is characterized by a low mutation rate (about 2 × 10 −10 mutations/bp/generation) (Ford et al., 2011), with an estimated evolutionary rate of 0.4—0.5 single nucleotide polymorphisms (SNPs)/genome/year and a divergence rarely higher than five SNPs in 3 years (Roetzer et al., 2013; Walker et al., 2013). Despite this low mutation rate, the number of drug resistant, especially MDR and XDR TB cases, due to the acquisition of mutations, is progressively increasing worldwide.…”
Section: Mutation Rate and Drug Resistance Acquisitionmentioning
confidence: 99%